Gender differences in socio‐demographics, clinical characteristic and quality of life in patients with schizophrenia: A community‐based study in Shenzhen. (16th December 2020) - Peng, Xiaodong; Wang, Shibin; Bi, Jianqiang; You, Liqin; Zhou, Zhijian; Tan, Wenyan; Xie, Haiyan; Hu, Chiyi; Ng, Chee H.; Liu, Tiebang
Abstract: Introduction: The objective of this study was to explore the gender differences of community‐dwelling patients with schizophrenia in terms of socio‐demographics, clinical characteristic and quality of life (QOL). Methods: A total of 433 community‐dwelling patients with schizophrenia were recruited in Shenzhen city, China. Data were obtained from a face‐to‐face interview with standard research questionnaire. The QOL and insight were assessed using the WHOQOL‐BREF and the Chinese version of the insight and treatment attitude questionnaire, respectively. Results: This cross‐sectional study included 206 male and 227 female patients. Male patients were more likely to be educated, employed, smoking cigarettes and drinking alcohol, and have an early age of illness onset. In contrast, female patients were more likely to be married/cohabitating and have drug side effects. There was no significant difference between genders across all QOL domain. Multiple regression analyzes showed that mental symptoms were negatively associated with all QOL domains, whereas frequency of exercise in the past year was positively associated with all QOL domains. Higher education levels, household per capita annual income in past year (≥100 000 RMB), employment status, IATQ score, drug side effects, marital status, and number of hospitalization were also significantly associated with specific QOL domains. Discussion: There was significant gender difference in socio‐demographics and clinical characteristics among community schizophrenia patients in Shenzhen city. Gender‐specific intervention measures are needed to improve the functioning and QOL in patients with schizophrenia.